Expert System For Diagnosing Eardrum (Tympanic Membrane) Diseases Using Certainty Factor Method - Jayanda, Prengky; Yulianti, Liza; Suryana, Eko (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Dr. M. Yunus Regional General Hospital Bengkulu is one of the hospitals in Bengkulu City that provides health service facilities. The current problem at the M. Yunus Regional General Hospital is the limited time available at the ENT Polyclinic and the delay in examining eardrum disease. So patients must go directly to the ENT Specialist Doctor who treats eardrum disease. The limited time of the Specialist Doctor who treats eardrum disease at the Hospital is also one of the causes of the delay in handling patients with eardrum disease. The expert system for diagnosing eardrum disease (tympanic membrane) using the certainty factor method at the M Yunus Regional General Hospital, Bengkulu City can be used as a container to help determine the diagnosis of eardrum disease based on the symptoms felt, and can make it easier for users to consult online via the link https://spakarmembrantimpanicf.site/. The expert system for diagnosing eardrum disease (tympanic membrane) using the certainty factor method at the M Yunus Regional General Hospital, Bengkulu City was created using the PHP programming language and MySQL database, which can be accessed online. Based on the black box method testing that has been carried out, it can be concluded that the functionality of the application has run well and this expert system can provide consultation results for the diagnosis of eardrum disease (tympanic membrane) through the Certainty Factor method stages based on the symptoms selected by the user during the consultation. Based on the alpha testing method testing that has been carried out, it can be concluded that this expert system is quite helpful for users in consultations and provides early detection information for the diagnosis of eardrum disease from the symptoms felt.